Calculation of the underground gas store functioning parameters in the water drive mode for maintenance of gas extraction process - Pyanylo, Ya.; Vavrychuk, P. (My University, 2016)
A model problem for the gas extraction process from UGS while substituting it with water is developed. The connection between the mass flowrate and pressure values in the main gas pipeline and on the outer water surface is established. A mathematic model for calculation of the UGS functioning parameters during the period of gas extraction is constructed. The results obtained are tested on the model problem. Розроблено модельну задачу процесу вiдбирання газу з ПСГ витiсненням його водою. Побудовано зв’язок мiж дебiтом свердловини та значеннями тискiв у магiстральному газопроводi та на зовнiшнiй межi води. Наведено формули розрахунку параметрiв роботи ПСГ пiд час вiдбирання газу. Отриманi результати апробовано на модельнiй задачi.
Розрахунок параметрiв роботи ПСГ для пiдтримування процесу вiдбирання газу
Keywords: underground gas store (UGS); mass flowrate; Bessel functions; gas-water contact (GWC); gas-compressor station (GCS); gas transportation system (GTS); пiдземне сховище газу (ПСГ); дебiт свердловини; функцiї Бес- селя; газо-водяний контакт (ГВК); компресорна станцiя (КС); газотранспортна система (ГТС); 5196:539.3